Spectroscopic and theoretical studies of jet‐cooled 3‐cyanoindole ammonia clusters in the gas phase. (7th February 2022) - Min, Ahreum; Kim, Jiwon; Moon, Cheol Joo; Ahn, Ahreum; Park, Juhyeon; Choi, Myong Yong
Abstract: The structural information of 3‐cyanoindole ammonia cluster, 3CI(NH3 )1, in molecular beams was investigated in the gas phase. We obtained UV–UV hole‐burning spectrum (UV–UV HB) to determine the number of conformers present in the molecular beams and examine their spectral features. As a result, single conformer of 3CI(NH3 )1 was observed in the mass‐selected one‐color resonant two‐photon ionization (1C‐R2PI) spectroscopy. The origin band of 3CI(NH3 )1 in the R2PI spectrum is redshifted by 122 and 71 cm −1 compared to those of the 3CI monomer and 3CI 1:1 water cluster, 3CI(H2 O)1, respectively. The fully optimized geometries, relative energies, transition energies, binding energies, and electrostatic potential (ESP) of the 3CI monomer, 3CI(H2 O)1, and 3CI(NH3 )1 clusters were calculated at the B3LYP and TD‐B3LYP methods with the 6‐311++(d, p) basis set. The observed spectra are compared with the predictions of time‐dependent density functional theory calculations. Abstract : The spectroscopic probe of 3CI ammonia cluster, 3CI(NH3 )1, has been investigated using mass‐selected one‐color resonant two‐photon ionization (1C‐R2PI) and UV–UV hole‐burning (UV–UV HB) spectroscopy obtained from a thermal evaporation method in the gas phase. The observed spectra are compared with the predictions of density functional theory (DFT) and time‐dependent DFT (TD‐DFT) calculations.